The Implementation of Human Rights in Conflict Management in the Papua Highlands During the Administration of Joko Widodo 2019-2024 - Sodiq Daulay, Istofa; Abdurraqif, Atep (Social Sciences and Humanities Reviews, 2025)
Background: The conflict in the Papua Mountains is a strategic national issue involving political, security, social, and human rights aspects. During Joko Widodo's administration from 2019 to 2024, Papua has been one of the national development priorities, but various reports indicate that violence and human rights violations against civilians continue to occur. Aims: This study aims to analyze the implementation of human rights principles in government policies related to conflict management in the Papua Mountains during Joko Widodo's administration from 2019 to 2024, as well as to identify the extent to which these policies are consistent with the principles of justice and conflict resolution. Methods: This research uses a qualitative approach with a normative legal research method. Data was collected through a literature review of legislation, policy documents, reports from national and international human rights institutions, and relevant academic literature. The analysis was conducted using a descriptive-qualitative method by comparing legal norms and human rights principles with policy practices in the field. Results: The results of the study indicate that the government has issued several important policies, namely the establishment of the Papua Pegunungan Province, the deployment of the Indonesian National Armed Forces (TNI) and the Indonesian National Police (Polri), the implementation of Limited Military Operations, and the acceleration of infrastructure and socio-economic development. These policies have contributed to security stability and improved community welfare. However, their implementation has raised various issues, including human rights violations against civilians, forced displacement, and regional development disparities. Conclusion: Conflict management in Papua Pegunungan during the 2019–2024 period demonstrates the state's commitment to ensuring security and development, but the implementation of human rights principles remains partial. A more humane, participatory, and equitable approach is needed to achieve sustainable conflict resolution in accordance with human rights principles and social justice